Enhanced light utilization in semitransparent organic solar cells based on a nonfullerene acceptor of IEICO-4F - Zang, Yue; Chen, Lingfeng; Zhou, Jintao; Xu, Rui; Liu, Zugang (Applied physics. A, Materials science & processing, 2021)
Although high efficiencies have been demonstrated in organic solar cells (OSCs), the development of semitransparent devices is still lagging behind due to the difficulty in making a balance between the active layer absorption and device transmittance. To address this challenge, a detailed study of semitransparent OSCs (ST-OSCs) based on the blends of the low bandgap polymer PTB7-Th and ultra-narrow bandgap nonfullerene acceptor IEICO-4F is carried out. Comprehensive optical modeling using the transfer matrix method (TMM) has been performed to assist the design of ST-OSCs and understand the effect of active layer composition and distributed Bragg reflectors (DBRs) on the device performance. By varying the PTB7-Th/IEICO-4F blending ratio from 1:1.5 to 1:3 and incorporating of DBRs, the average visible transmittance (AVT) of the ST-OSCs was dramatically increased by over 26% with a slight decrease in photocurrent ( J max ) less than 5%. This significant improved light utilization can be attributed to the enhanced photon harvesting of NIR range and decreased visible light absorption by increasing the IEICO-4F content, as well as the optimal optical properties in the ST-OSCs with the use of DBRs. Our results can provide a feasible way to optimize the light harvesting and transmittance of the device for achieving high-performance ST-OSCs.